Standardized technique for single port laparoscopic ileostomy and colostomy. (July 2014) - Shah, A.; Moftah, M.; Hadi Nahar Al‐Furaji, H.; Cahill, R. A.
Abstract Aim Single site laparoscopic techniques and technology exploit maximum usefulness from confined incisions. The formation of an ileostomy or colostomy seems very applicable for this modality as the stoma occupies the solitary incision obviating any additional wounds. Method Here we detail the principles of our approach to defunctioning loop stoma formation using single port laparoscopic access in a stepwise and standardized fashion along with the salient specifics of five illustrative patients. No specialized instrumentation is required and the single access platform is established table‐side using the 'glove port' technique. Results The approach has the intra‐operative advantage of excellent visualization of the correct intestinal segment for exteriorization along with direct visual control of its extraction to avoid twisting. Postoperatively, abdominal wall trauma has been minimal allowing convalescence and stoma care education with only one parietal incision. Conclusion Single incision stoma siting proves a ready, robust and reliable technique for diversion ileostomy and colostomy with a minimum of operative trauma for the patient.